Impact mechanics of multilayer composite armors: Analytical modeling, FEM numerical simulation, and ballistic experiments. (1st October 2022) - Signetti, Stefano; Ryu, Seunghwa; Pugno, Nicola M.
Abstract: An analytical model is developed to study the ballistic behavior of multilayer composite armors subjected to the high-velocity impact of projectiles with arbitrary angle of incidence, shape, size, and frictional characteristics. The thickness compaction resulting from the production process is also accounted for, quantifying the role of the curing pressure on the enhancement of the impact toughness of composite laminates. Finite element method simulations are used in a complementary manner to study damage and failure mechanisms within the targets. Both approaches are validated by extensive experimental ballistic tests on multilayer composite targets. The role of the layer stacking sequence is also investigated. It emerges that graded multilayer configurations yield higher toughness when the projectile penetrates plies with decreasing fracture strength. These results can explain common structural arrangements in biological armors as well as be exploited in the design and optimization of shielding structures against high-velocity projectiles.